Selvinkriminering og oplysningspligter - Langsted, Lars Bo (Nordisk Tidsskrift for Kriminalvidenskab, 1998)
The article deals with the area where the legal safeguards against self-incrimination collide with legal obligations to produce information and material to administrative bodies. As far as the privilege against self-incrimination is concerned, Danish law not only allows the accused to refuse to give evidence in the criminal case against him but also provides him with the right not to tell the truth, if he chooses to take the stand. On the other hand, Danish administrative laws contain a lot of rules according to which citizens are obliged to produce information and material. In cases of refusal or untrue information criminal sanctions can be imposed. The cases of Saunders and Serves from the European Court of Human Rights are examined and compared to Danish and Norwegian law. It is concluded that neither Norwegian nor Danish law is in total conformity with the Saunders case, although the precise extent of the Saunders case is rather dim. Norwegian case law for instance allows prosecution to make use of reports made by administrative bodies containing explanations given by the (now) accused person to a certain extent, and Danish case law has so far stated that the legal obligations to give information to administrative organs are still applicable even after a charge has been raised against the person in question. It is not possible, however, to punish the giving of false informations and statements by that person, given after criminal charges have been raised against him. Finally, the author recommends that the legislator now takes upon him the difficult task of creating a general set of rules safeguarding the rights of the citizens without giving up the fundamental obligation to provide the administration with information needed. At the same time it is recommended that the legislator narrows the possibilities of using administrative penal sanctions in order to recreate the clean cut between administration and prosecution.